Assessment of leopard translocations in South Africa - McManus, Jeannine; Faraut, Lauriane; Couldridge, Vanessa; van Deventer, Jaco; Samuels, Igshaan; Cilliers, Deon; Devens, Carolyn; Vorster, Paul; Smuts, Bool (Frontiers in Conservation Science, 2022)
Translocations are commonly employed to mitigate human-carnivore conflict but rarely evaluated, resulting in conflicting reports of success, particularly for leopards (Panthera pardus). We evaluate available leopard translocation data, the factors driving the intentional removal of leopards, and potential causal factors associated with successful and failed translocation events. We obtained data on 60 leopard translocation events across five provinces in South Africa between 1994 and 2021. We considered a successful translocation outcome when (1) the animal was moved outside of its original home range, (2) established a new home range away from the capture site, (3) no substantive livestock losses were linked to the translocated animal in the post release monitoring period, and (4) the animal survived at least six months post translocation. If mortality occurred due to factors that were equally likely to impact resident individuals, and were unrelated to the translocation event (e.g., poaching) the event was not considered a failed effort. Most translocations were the result of human-carnivore conflict (HCC; 82%, n = 49), stressing the high prevalence of HCC, and the importance of advocating preventative conflict mitigation efforts. Leopards were moved distances from 2.5 to 196.3 km (63.3±51.7km). Forty (67%) translocation events had unknown outcomes, indicating the limited data available on translocation outcomes. This also indicates the disparity in objectives of translocations by various entities involved with translocations and suggests that monitoring be a prerequisite for future translocations. Twenty events offered reliable outcomes by means of post event monitoring, with seven (12%) considered successful, three (5%) as failures, four (7%) were not moved beyond their original home ranges, while six (8%) ended in unrelated deaths. Failed events were attributed to inter/intra-specific competition, and one animal returned to its original home range after a translocation distance of 68km. Translocation success was strongly explained by translocation distance. We found that damage-causing leopards were successfully translocated under specific conditions, and longer translocation distances increase success. Translocations are commonly employed but are still poorly monitored. We discuss basic standardised protocols to improve future leopard translocations (including pre- and post-monitoring) while advocating alternative, non-lethal practices to reduce the prevalence of human-carnivore conflict.